2010
DOI: 10.1016/j.wasman.2010.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Field scale evaluation of volatile organic compound production inside biosecure swine mortality composts

Abstract: Emergency mortality composting associated with a disease outbreak has special requirements to reduce the risks of pathogen survival and disease transmission. The most important requirements are to cover mortalities with biosecure barriers and avoid turning compost piles until the pathogens are inactivated. Temperature is the most commonly used parameter for assessing success of a biosecure composting process, but a decline in compost core temperature does not necessarily signify completion of the degradation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Gases generated inside compost can also provide useful information about the status of the biomass decay process and could potentially be exploited to optimize and control the process. The concept of using compost gases for the non-invasive, biosecure monitoring of decay process completion has been used for disposal of potentially infectious animal carcasses [9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Gases generated inside compost can also provide useful information about the status of the biomass decay process and could potentially be exploited to optimize and control the process. The concept of using compost gases for the non-invasive, biosecure monitoring of decay process completion has been used for disposal of potentially infectious animal carcasses [9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Another concern was monitoring the progress and completion of the process without removing the cover. Volatile organic compounds (VOCs) were used as biomarkers of decaying mortalities (Akdeniz et al, 2011(Akdeniz et al, , 2010a(Akdeniz et al, , 2010b(Akdeniz et al, , 2009. Other researchers also recognized the importance of predicting the maturity of the biosecure composting systems.…”
Section: Research On Composting Avian Influenza Infected Mortalitiesmentioning
confidence: 99%
“…Results of the VOC study are reported in papers by Akdeniz et al (2010aAkdeniz et al ( , 2010bAkdeniz et al ( , 2011.…”
Section: Introductionmentioning
confidence: 99%